Electromagnetic scattering analysis of coated conductors with edges using the method of auxiliary sources (MAS) in conjunction with the standard impedance boundary condition (SIBC). - Anastassiu, H.T (IEEE Transactions on antennas and propagation)
A novel combination of the method of auxiliary sources (MAS) and the standard impedance boundary condition (SIBC) is employed in the analysis of transverse magnetic (TM) plane wave scattering from infinite, coated, perfectly conducting cylinders with square cross sections. The scatterer is initially modeled by a SIBC surface and the scattering mechanism is subsequently analyzed via MAS. Although SIBC as well as MAS possess theoretical limitations with regard to an edge, the numerical results show that the MAS/SIBC method provides results of high accuracy for a range of structures with edges. The SIBC modeling of coated conductors with edges has previously been investigated in the literature and thus, this work focuses on comparing MAS and the method of moments (MoM) for SIBC surfaces (MoM/SIBC). A detailed complexity analysis shows that the MAS/SIBC method is, under certain conditions, more efficient than the MoM/SIBC method, proving that the proposed novel combination is a powerful and advantageous computational tool